Laporan Hasil Asesmen Diagnostik Non-Kognitif: Identifikasi Sosial Emosional dan Gaya Belajar Peserta Didik di SMA Negeri 3 Kejuruan Muda - Juwita Syafrida Yanti; Ela Mentari (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
It is important to understand that students' academic achievement is not only influenced by their cognitive abilities, but also by non-cognitive factors such as social-emotional skills and learning styles. In an effort to improve the quality of education and facilitate the optimal development of students at SMA Negeri 3 Kejuruan Muda, it is hoped that the report on the results of the non-cognitive diagnostic assessment can be a strong foundation for SMA Negeri 3 Kejuruan Muda in developing holistic, adaptive, and student-centered learning strategies. Through a better understanding of the social-emotional aspects and learning styles, schools can create a learning environment that supports not only academic achievement, but also students' optimal personal and social development. Thus, this study aims to (1) Identify students' social-emotional abilities and areas that require further support. (2) Assess students' learning styles to adjust teaching methods to their preferences. (3) Provide recommendations based on assessment results to improve support and learning strategies in schools. This study uses a qualitative descriptive approach with data collection through a google form questionnaire distributed to all students of SMA Negeri 3 Kejuruan Muda. The results of the study showed that 10.5% of students had high social emotional abilities, 60.5% of their social emotional abilities were said to be sufficient, 27.8% needed improvement and 1.2% needed significant development by BK teachers or counselors. Meanwhile, the Learning Styles possessed by students at SMAN 3 Kejuruan Muda were 40% Visual learning style, 30% Auditory learning style and 30% Kinesthetic learning style. Furthermore, the recommended treatment recommendations for students with high levels of social emotional abilities are to become peer counselors, students who have moderate social emotional abilities can be guided by peer counselors and students who have low levels of social emotional abilities require guidance by BK teachers or professional counselors. Meanwhile, recommendations for visual learning styles can be presented with learning media in the form of images, videos or slides, auditory learning styles are presented with learning media in the form of audio recordings or listening to explanations from teachers and kinesthetic learning styles can be included in games, simulations, practicums, projects and demonstrating learning materials.